Percepção socioambiental de pescadores artesanais da Bacia de Campos (RJ) : aplicação de um modelo de equações estruturais multinível. - Diogo Cesar Pereira (2022)
The goal of this dissertation is to investigate the socio-environmental perception of artisanal fishermen from Campos Basin, Rio de Janeiro, in the Pescarte environmental education project. The research is based on data from the Pescarte Census, carried out with artisanal fishermen from seven municipalities in the Campos Basin, Rio de Janeiro, between 2014 and 2016. In this way, it proposes an approach to the development of multilevel structural equation models, a multivariate method characterized by the joint use of factor analysis, multivariate regression, path analysis and hierarchical modeling. In this way, a latent variable of socio-environmental perception was created from observed variables related to the economic, environmental and socio-environmental conflict dimensions of artisanal fishing. In the deterministic part of the model, two latent variables related to the Structural Context and the relational context of artisanal fisheries were created. Among the main results, it was found the prevalence of the influence of the Relational Context of artisanal fisheries on the socio-environmental perception of artisanal fishermen compared to the influence of the Structural Context. Furthermore, it was verified the existence of an indirect effect exerted by the Structural Context on the socio-environmental perception, mediated by its association with the Relational Context. Finally, it was not possible to support the hypothesis of the influence of local contexts, represented by the municipal development index, on the socio-environmental perception of artisanal fishermen. Based on the results, the potential of the methodology applied to measure and explain the socio-environmental perception of artisanal fishermen was verified, as well as, the addition to the potential of this methodology with other research objects related to socio-environmental perceptions. It is worth noting that this Master’s Thesis is a product of a research financed by the Pescarte Environmental Education Project (PEA), which is a mitigation measure required by the Federal Environmental Licensing Rules, conducted by IBAMA.